The implementation of distance education models in higher мedical schools - N. G. Goncharova; E. V. Kirsanova; A. A. Svetlicky (Zaporozhye State Medical University, 2014)
The computer's technological revolution over the last years has entered all spheres of human society and has given new guidelines in the education requirements. New knowledge requires new adoption methods. The article solves actual problem associated with the exchange, association and generalization of scientifi c and pedagogical experience of innovative technologies in the educational process of higher medical schools. Methodological signifi cance of the work is determined by the high rate of distance learning use in the process of medical students training. The article discusses fi ve current models of distance learning and the expediency of distance education in higher Medical schools is explained.